Application of ultrasound‐guided cholecystocentesis to the evaluation of the metabolite profiling in bile of dogs and cynomolgus monkeys. Issue 3 (27th May 2019) - Dierks, Elizabeth A.; Luk, Chiuwa E.; Cai, Hong; MacGuire, Jamus; Fox, Maxine; Smalley, James; Fancher, R. Marc; Janovitz, Evan; Foster, Kimberly; Sun, Qin
Abstract: In this study, we describe a novel approach for collecting bile from dogs and cynomolgus monkeys for metabolite profiling, ultrasound‐guided cholecystocentesis (UCC). Sampling bile by UCC twice within 24 hours was well tolerated by dogs and monkeys. In studies with atorvastatin (ATV) the metabolite profiles were similar in bile obtained through UCC and from bile duct‐cannulated (BDC) dogs. Similar results were observed in UCC and BDC monkeys as well. In both monkey and dog, the primary metabolic pathway observed for ATV was oxidative metabolism. The 2‐hydroxy‐ and 4‐hydroxyatorvastatin metabolites were the major oxidation products, which is consistent with previously published metabolite profiles. S‐cysteine and glucuronide conjugates were also observed. UCC offers a viable alternative to bile duct cannulation for collection of bile for metabolite profiling of compounds that undergo biliary excretion, given the similar metabolite profiles in bile obtained via each method. Use of UCC for metabolite profiling may reduce the need for studies using BDC animals, a resource‐intensive model.